2019
DOI: 10.1021/acs.jced.9b00052
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of DNP-Amino Acids in New Biodegradable Choline Amino Acid/Ionic Liquid-Based Aqueous Two-Phase Systems

Abstract: In this work, the partitioning of four N-(2,4dinitrophenyl)-amino acids (DNP-L-leucine, DNP-L-valine, DNP-L-alanine, and DNP-glycine) in aqueous two-phase systems (ATPS) containing a new biodegradable ionic liquid cholinium alaninate, [Ch][Ala], and the inorganic salts K 3 PO 4 and K 2 HPO 4 was determined at T = 298.15 K and p = 101.3 kPa. The influence of the salt on the partition coefficients was discussed. The distribution coefficients (K) of the four studied DNP-amino acids are higher in the ATPS containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…, ionic liquids based on amino acids and choline (essential nutrient), were developed. CAAILs, first synthesized by Moriel et al , combine a quaternary amine as cation (choline) with the carboxylic functional group of amino acids and present lower toxicity and higher biocompatibility compared to the classical ionic liquids, such as the ones based on imidazolium, pyrrolidinium, and pyridinium cations. Moreover, CAAILs can be produced in a relatively cheap fashion and taking advantage of natural and easily available resources, given that choline is a B-complex nutrient and that amino acids are the building blocks of proteins, decreasing the environmental impact of solvent synthesis. , Similarly to API-ILs, CAAILs have also been used to increase the solubility of poorly water-soluble drugs such as lamotrigine, improving the design of crystallization processes and allowing the validation of thermodynamic models . Furthermore, CAAILs have been effectively applied in the partition of biomolecules, such as amino acids, proteins, antioxidants, , and pigments, in biomass valorization, , and in carbon dioxide capture , and are considered outstanding biocompatible media for biocatalytic applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ionic liquids based on amino acids and choline (essential nutrient), were developed. CAAILs, first synthesized by Moriel et al , combine a quaternary amine as cation (choline) with the carboxylic functional group of amino acids and present lower toxicity and higher biocompatibility compared to the classical ionic liquids, such as the ones based on imidazolium, pyrrolidinium, and pyridinium cations. Moreover, CAAILs can be produced in a relatively cheap fashion and taking advantage of natural and easily available resources, given that choline is a B-complex nutrient and that amino acids are the building blocks of proteins, decreasing the environmental impact of solvent synthesis. , Similarly to API-ILs, CAAILs have also been used to increase the solubility of poorly water-soluble drugs such as lamotrigine, improving the design of crystallization processes and allowing the validation of thermodynamic models . Furthermore, CAAILs have been effectively applied in the partition of biomolecules, such as amino acids, proteins, antioxidants, , and pigments, in biomass valorization, , and in carbon dioxide capture , and are considered outstanding biocompatible media for biocatalytic applications …”
Section: Introductionmentioning
confidence: 99%
“…17,18 Similarly to API-ILs, CAAILs have also been used to increase the solubility of poorly watersoluble drugs such as lamotrigine, 22 improving the design of crystallization processes and allowing the validation of thermodynamic models. 23 Furthermore, CAAILs have been effectively applied in the partition of biomolecules, such as amino acids, 19 proteins, 24 antioxidants, 25,26 and pigments, 27 in biomass valorization, 21,28 and in carbon dioxide capture 21,29 and are considered outstanding biocompatible media for biocatalytic applications. 30 In this work, the goal was to assess the influences of the mole fraction of ionic liquid and of temperature on the thermophysical properties of binary mixtures containing water, ethanol or propan-1-ol and cholinium L-alaninate ([Ch] were also delved into.…”
Section: Introductionmentioning
confidence: 99%
“…In this essay, the UNIQUAC model was used to represent the tie-line compositions. This model was selected because although it was not developed for systems containing electrolytes, it has been demonstrated to be very suitable for ATPSs containing ionic liquids with organic or inorganic salts , and LLE of polymer–salt systems. The UNIQUAC model requires the volume, r i , and surface area q i, parameters for each pure component i .…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, the extraction distribution behavior also fluctuates with pH value, which is also very beneficial to the reverse extraction process. Requejo et al [11] determined the partition coefficients of four N-(2,4-dinitrophenyl)-amino acids (leucine, valine, alanine, and glycine) in aqueous biphasic system containing a new biodegradable ionic liquid cholinium alaninate [Ch][Ala]. The results showed that the increase of the length of the connecting line led to the increase of K value.…”
Section: Extraction and Separationmentioning
confidence: 99%